Shen Shuai II recipe improves renal hypoxia to attenuate renal injury in 5/6 renal ablation/infarction rats and effect evaluation using blood oxygenation level-dependent functional magnetic resonance imaging - Yizeng Xu; Fang Lu; Meng Wang; Lingchen Wang; Chaoyang Ye; Shuohui Yang; Chen Wang (Renal Failure)
Background Renal hypoxia plays a key role in the progression of chronic kidney disease (CKD). Shen Shuai II Recipe (SSR) has shown good results in the treatment of CKD as a common herbal formula. This study aimed to explore the effect of SSR on renal hypoxia and injury in CKD rats.Methods Twenty-five Wistar rats underwent 5/6 renal ablation/infarction (A/I) surgery were randomly divided into three groups: 5/6 (A/I), 5/6 (A/I) + losartan (LOS), and 5/6 (A/I) + SSR groups. Another eight normal rats were used as the Sham group. After 8-week corresponding interventions, blood oxygenation level-dependent functional magnetic resonance imaging (BOLD-fMRI) was performed to evaluate renal oxygenation in all rats, and biochemical indicators were used to measure kidney and liver function, hemoglobin, and proteinuria. The expression of fibrosis and hypoxia-related proteins was analyzed using immunoblotting examination.Results Renal oxygenation, evaluated by BOLD-fMRI as cortical and medullary T2* values (COT2* and MET2*), was decreased in 5/6 (A/I) rats, but increased after SSR treatment. SSR also downregulated the expression of hypoxia-inducible factor-1α (HIF-1α) in 5/6 (A/I) kidneys. With the improvement of renal hypoxia, renal function and fibrosis were improved in 5/6 (A/I) rats, accompanied by reduced proteinuria. Furthermore, the COT2* and MET2* were significantly positively correlated with the levels of creatinine clearance rate (Ccr) and hemoglobin, but negatively associated with the levels of serum creatinine (SCr), blood urea nitrogen (BUN), serum cystatin C (CysC), serum uric acid (UA), 24-h urinary protein (24-h Upr), and urinary albumin:creatinine ratio (UACR).Conclusion The degree of renal oxygenation reduction is correlated with the severity of renal injury in CKD. SSR can improve renal hypoxia to attenuate renal injury in 5/6 (A/I) rats of CKD.